Riesgo, recursos naturales y discursos : el debate en torno a las tecnologías y el ambiente en América Latina (Tecnología y Sociedad, 2019)
We argue here that Latin America is going through a cycle of environmental protest, as a result of two opposite forces. On the one hand, the increasing global appetite for natural resources –food, fibres, minerals, energy– has intensified the pressure on the environment in the region. After decades of neoliberal globalization, key actors in these processes are transnational corporations. On the other hand, civil society and social movements are well organized and active in responding to the social and environmental risks, in terms of both material and discursive resources. We situate our research in the confluence of three theoretical perspectives: world systems theory, contentious politics, and resistance to technologies.
Keywords: Latin America; Risk; Environment; Contentious politics; Resistance to technologies